Competency-Based Reward System in Project-Based Organization: Empirical Study from Tunisia - Hedhili, Mohamed Ali; Boudabbous, Sami (International Journal of Business, Economics and Management, 2021)
The traditional reward system (RS) based on the job description and salary scales is often unable to cope with changes in the business environment: market globalization, technological development, and organizational changes. In this context, the project-based organization (PBO) must adopt new RSs that encourage employees to have responsibility and autonomy in their jobs and define their professional lifestyle. The present work aimed to identify the challenges of a competency-based reward system (CBRS) in PBO. To this end, we carried out a qualitative study based on 31 semi-structured interviews with Tunisian project managers. The results showed that RS must fund the development of the project actor, emphasizing their current and potential competencies rather than rewarding past performance. In addition, RS may be a substantial risk in PBO when there is a significant gap between employees’ salaries. Improper distribution of rewards can negatively affect the motivation of project team members and encourage unproductive functioning within the organization.